Equine-assisted therapy effectiveness in improving emotion regulation, self-efficacy, and perceived self-esteem of patients suffering from substance use disorders - Nagwa Souilm (BMC, 2023)
Abstract Substance Use Disorders (SUD) is a universal overwhelming public health problem and is associated with other psychological and mental health ailments such as emotion regulation, perceived self-esteem, and self-efficacy problems. Complementary and alternative medicine may be beneficial. The aim of this study was to assess the effectiveness of equine-assisted therapy in improving emotion regulation, self-efficacy, and perceived self-esteem among patients suffering from substance use disorders. It was carried out using a randomized controlled trial design at Behman hospital, Cairo, Egypt. It included 100 patients suffering from SUD attending the setting, equally randomized into an intervention group to receive the equine assisted therapy and a control group to receive the regular care. Data were collected using a self-administered questionnaire with standardized tools for assessment of emotion regulation, General Self-Efficacy (GSE), and perceived self-esteem. The intervention group received weekly equine-assisted therapy sessions over 6 weeks in addition to their standard regular therapy. Patients in both groups had similar demographic and SUD characteristics, as well as baseline scores of reappraisals, suppression, GSE and perceived self-esteem. At post-intervention, the intervention group had significant improvements in all these scores in comparison with the control group, as well as their baseline. The multivariate analysis identified the study intervention as a significant positive predictor of the reappraisal and GSE scores, and a negative predictor of the suppression and perceived self-esteem negative score. In conclusion, equine assisted-therapy as a complementary treatment in patients suffering from SUD is effective in improving their emotion regulation, self-efficacy, and perceived self-esteem. A wider use of this approach is recommended in SUD patients along with provision of needed facilities and resources, and training nurses in its administration. Further research is proposed to assess its long-term effectiveness. The clinical trial was registered in the "Clinical Trials.gov Protocol Registration and Results System (PRS);" registration number is (05632185/2022) and the full date of first registration is 10/11/2022.